Card Game as an Educational Strategy in Software Testing: Debug a game to explore content on Levels and Types of Testing - Costa, Carolina de Melo; Aguiar, Yuska Paola Costa; Souza, Luiz Gusttavo Oliveira de; Morais, Jayanne Laysa Cruz; Silveira, Pedro Alves da (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2024)
In the teaching of Software Quality, maintaining student engagement is a challenge when the educational strategies adopted are classical and predominantly theoretical. The use of playful approaches that encourage hands-on practice through creative activities has been increasingly recognized for its potential in the educational field. With the goal of working on introductory topics about types and levels of testing, an activity was proposed to be carried out over the course of three classes, in-person and in teams, where the students had to create card games on the topic. The teams had the freedom to choose between creating original games or adapting existing ones. In total, six games were proposed and tested by the class. On the occasion, after using the games, suggestions for improvement were identified, the "favorite game" was chosen, and the lessons learned were listed. The game Debug, the most voted, was selected to exemplify the artifacts generated during the activity. From the teacher’s perspective, it was possible to notice the students’ engagement in the creation and application of the games. At the end, the class could express their perception of the activity’s usefulness and suggest improvements for future editions.